REDUCING UNJUSTIFIED COSTS BY USING VALUE STUDIES AND FUNCTIONAL ANALYSIS (A FIELD STUDY) - Maytham Hazim Azeez Khzaee; Nuha Aadi Abd Ali; Alaa Miran Hussein (Galaxy International Interdisciplinary Research Journal, 2024)
There are several factors putting a lot of strain on the Iraqi economic units, including higher product costs and lower product merit, given the fierce competition that the units are currently facing as a result of multiple competitors entering the market and offering products at lower costs, better functional performance, and higher quality than local products. Thus, the study focused on the application of value engineering and its potential to reduce costs and increase product value in the Najaf factory that makes men’s clothes. This was carried out in an attempt to alleviate the difficulties the firm has due to its reliance on traditional cost-control methods.